Methods of Teaching Ethics of Water Use in Water Economy - Mirzaev Sanjar Olimovich; Saloyiddinov Umid Shamsiddin ugli (International Journal on Integrated Education, 2023)
Current work of analyst and otuv hadjaligida Suwan folgirendanish-etikaseli ura-leikatoni. Narodotourist leadership and Global suv cooperation, irrigation and drainage Commission and Orl dengizi and Volbondy on the territory of Uchun special Trust foundation, suv khujaligida of auxiliary significance. Dilalar and shvchilar uchnsya_ both times were present at the ethylgan proposal.